2018
DOI: 10.1039/c8sc01093e
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free borylative dearomatization of indoles: exploring the divergent reactivity of aminoborane C–H borylation catalysts

Abstract: We report the first example of catalytic dearomatization of indoles to generate 3-borylindolines using metal-free borane catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…The importance of the steric hindrance in this kind of catalysts has also been studied . Interestingly, when 1‐tosyl indoles were used as the starting substrates, borylative dearomatization products were obtained (Scheme b) . In mechanistic studies, Fontaine and co‐workers found the barrier to hydroboration (25.9 kcal mol −1 ) is lower than the barrier to C−H activation (27.8 kcal mol −1 ) when 1‐arylsulfonyl indoles are used as the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of the steric hindrance in this kind of catalysts has also been studied . Interestingly, when 1‐tosyl indoles were used as the starting substrates, borylative dearomatization products were obtained (Scheme b) . In mechanistic studies, Fontaine and co‐workers found the barrier to hydroboration (25.9 kcal mol −1 ) is lower than the barrier to C−H activation (27.8 kcal mol −1 ) when 1‐arylsulfonyl indoles are used as the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The syn addition and related high diastereoselectivity was previously evidenced from the X-ray crystallographic characterization of the products derived from the borylative dearomatization of 2-methyl substituted 1-phenylsulfonyl indoles such as 7n and 7o. 25 Despite all substrates and the precatalyst 2F being solids, none of the catalytic reactions needed a solvent medium. The 100 °C was found to be an optimal temperature for this transformation since the reactions conducted at 80 °C required a longer reaction time (~ 36 h).…”
Section: Borylation and Borylative Dearomatization Of Heteroarenes Onmentioning
confidence: 99%
“…In a subsequent report, we have demonstrated that all these catalysts and BH3.SMe2 can promote the borylative dearomatization reaction when using electron-poor arylsulfonyl indoles as substrates and HBpin as reagent, leading to the formation of 3-boronyl indoline products (Scheme 1b), through a 1,2-hydroboration/backbone redistribution mechanism (Figure 1b). 25 Such products can be viewed as potential synthetic intermediates for several pharmaceuticals, natural products, and materials. 26 Herein we report the progress we made in optimizing our metal-free methodology for borylation and borylative dearomatization of heteroarenes suitable for an industrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis of different types of organoboron compounds continues to be an important research field [14,15,16,17,18,19,20]. Conventional methods for their preparation are based on either reactive organometallic reagents or transition-metal-mediated processes [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Recently, great effort has been made towards the development of transition-metal-free methods with high chemoselectivity or regioselectivity and environmental sustainability [38,39,40,41,42,43,44,45,46,47,48].…”
Section: Introductionmentioning
confidence: 99%